Spontaneous occlusion of the circle of Willis in a young woman with epilepsy: epileptic-type moyamoya disease. (15th May 2012) - Shrivastava, Makardhwaj Sarvadaman; Khullar, Vikas; Singh, Mini; Haneef, Mohammed; Nag, Nalin
Abstract : The authors report a case of a 31-year-old woman from India with history of seizure disorder who presented with sudden onset right hemiparesis and right-sided upper motor neuron type facial palsy. No identifiable risk factors were noted on admission and all laboratory investigations were negative. MR angiography helped in arriving at the diagnosis of moyamoya disease as the aetiology of her symptoms.